Political Parties and the Problems of Role and Functions in Comparative Political Systems - Hacene, Abderrazak (Journal of Legal Studies and Researches, 2022)
This study examines the importance of the role of parties in the political life of countries. She revealed that contemporary political thought has differed about the extent to which parties are necessary or dangerous for democracy It concluded that he has not yet found a better means for political competition and to promote the national interest than the parties.